Connectivity of Dinoyo Ceramic Tourism Kampong Based on Space Syntax Analysis - Nurjanah Ratnaningrum; Ema Yunita Titisari; Antariksa Antariksa (Journal of Artificial Intelligence in Architecture, 2026)
Dinoyo Ceramic Tourism Kampong in Malang City has been a significant centre for ceramic craftsmanship since the 1930s, blending industrial activities with cultural tourism. However, the village faces connectivity challenges in spatial management, including narrow roads, limited public facilities, and complex circulation patterns that hamper accessibility and the visitor experience. The objective of this research is to analyse the spatial connectivity of the kampong using the Space Syntax method (DepthMapX software) to identify problematic areas and propose improvements. Space Syntax analysis (focusing on the connectivity parameter) reveals that linear, well-connected circulation patterns encourage higher spatial clarity and social interaction. In contrast, areas with many branching routes and no clear open spaces reduce users’ ability to comprehend and navigate the village effectively. The connectivity analysis highlights key circulation nodes (segments) that act as essential connectors, while also identifying multiple segments with very low connectivity due to their fragmented and dead-end layout. These findings suggest that targeted spatial interventions—such as adding strategic footpaths, widening or linking dead-end alleys, improving signage, and managing vehicle traffic—could significantly improve road connectivity and spatial legibility. By implementing these post–Space Syntax recommendations, the kampong’s visitor movement and circulation can be enhanced, supporting sustainable tourism development and improving the spatial management of the Dinoyo Ceramic Tourism Kampong as an educational and cultural destination.